1980
DOI: 10.1111/j.1476-5381.1980.tb10900.x
|View full text |Cite
|
Sign up to set email alerts
|

INTERACTION BETWEEN SYNTHETIC ANALOGUES OF QUINOXALINE ANTIBIOTICS AND NUCLEIC ACIDS: ROLE OF THE DISULPHIDE CROSS‐BRIDGE AND d‐AMINO ACID CENTRES IN DES‐N‐TETRAMETHYL‐TRIOSTIN A

Abstract: I [Ala3, Ala'] TANDEM is an analogue of des-N-tetramethyl-triostin A (TANDEM) in which both L-Cys residues of the octapeptide ring are replaced by L-Ala; accordingly it lacks the disulphide cross-bridge which limits the conformational flexibility of TANDEM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…In the event neither of these notions proved to be correct. Most probably the conformation of the depsipeptide in solution is different from that of either triostin A or ANDEM; the asymmetric peptide ring may be twisted in such a way that the quinoxaline chromophores are no longer positioned roughly parallel to allow for bifunctional intercalation into the DNA helixlike the situation previously postulated for L-serine-containing analogues of TANDEM [6,13].…”
Section: Discussion [N-meval4]tandemmentioning
confidence: 98%
See 2 more Smart Citations
“…In the event neither of these notions proved to be correct. Most probably the conformation of the depsipeptide in solution is different from that of either triostin A or ANDEM; the asymmetric peptide ring may be twisted in such a way that the quinoxaline chromophores are no longer positioned roughly parallel to allow for bifunctional intercalation into the DNA helixlike the situation previously postulated for L-serine-containing analogues of TANDEM [6,13].…”
Section: Discussion [N-meval4]tandemmentioning
confidence: 98%
“…The cysteine -NH groups do not therefore appear to play an important role in either holding the peptide portion of the antibiotic in any particular conformation, or in determining the sequence-selectivity of the ligand. In fact [Ala3, Ala7]TANDEM, a compound lacking a cross-bridge altogether, has been shown to interact with DNA (albeit weakly) and again displays the same AT specificity as does TANDEM [13]. It seems likely that the function of the cysteine residues in providing the cross-bridge is to restrict the conformational flexibility of the peptide ring so as to reduce unfavourable entropy terms in the binding reaction, rather than to participate in direct interactions with functional groups on the DNA.…”
Section: Discussion [N-meval4]tandemmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding the interaction of artificial molecules with poly(rA), Manzini et al [44] found that the compound known as 4',6diamidino-2-phenylindole dihydrochloride (DAPI, Figure 7) can bind double helical poly(rA). Similarly, synthetic analogues of quinoxaline are also able to bind poly(rA)•poly(rU) complexes [45], while other artificial compounds such as ethidium salts, quinacrine, and proflavine proved to be efficient binders of single-stranded poly(rA) capable of inducing self-structures of such RNA. This characteristic is absent in the compound Hoechst 33258 that acts as a poly(rA) binder, but is unable to provoke structural organization in the same RNA [46].…”
Section: Synthetic Organic Moleculesmentioning
confidence: 99%
“…Similarly, synthetic analogues of quinoxaline are also able to bind poly(rA)·poly(rU) complexes [ 45 ], while other artificial compounds such as ethidium salts, quinacrine, and proflavine proved to be efficient binders of single-stranded poly(rA) capable of inducing self-structures of such RNA. This characteristic is absent in the compound Hoechst 33258 that acts as a poly(rA) binder, but is unable to provoke structural organization in the same RNA [ 46 ].…”
Section: Reviewmentioning
confidence: 99%